Unfolding the Mild to Moderate Short-Term Side Effects of Four COVID-19 Vaccines Used in Bahrain: A Cross-Sectional Study - Muhammad Nauman Zahid (MDPI AG, 2021)
Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) created a global pandemic (COVID-19) that has resulted in massive health and economic losses. The current unavailability of treatments leaves vaccination as the only way to control this disease. There are four vaccines (Sinopharm, Pfizer—BioNTech, Sputnik, and AstraZeneca) available in Bahrain. This project aimed to study the most common side effects resulting from the first and second doses of these four vaccines. Data were collected through an online questionnaire answered by 311 individuals who received both doses of one of these four vaccines. The results of this study revealed that regardless of the vaccine identity, participants experienced more side effects from the second dose. Among the different side effects, pain at the site of injection was primarily observed after the first dose of the Pfizer vaccine (43%), which was followed by the AstraZeneca vaccine (31%). Moreover, fever was observed in participants after the first dose of the Sputnik vaccine (37%), while headache was mainly observed after the first dose of the Pfizer vaccine (32%). It is important to note that fatigue was observed after the first dose of all four vaccines but was reported by the highest proportion of respondents in the Pfizer group (28%). Interestingly, there are some side effects, such as pain at the site of injection, that are correlated with fever (r = 0.909). Similarly, headache is correlated with fever (r = 0.801) and pain at the site of injection (r = 0.868). Overall, it was observed that recipients of the Sinopharm vaccine reported the mildest side effects among all four vaccines. The crucial finding of this study is that the first and second dosage post-vaccination side effects were modest and predictable with no occurrences of hospitalization; this information can assist in lessening vaccine apprehension.